Usage of Acmeology Methodology in the Research of Psychology of the Family - Posvistak, Olesya (Psychological Prospects Journal, 2016)
The object field of family acmeology and family psychology is defined in the article on the base of the analysis of scientific sources and literature that allowed to define in what way these two scientific fields correlate. The possibility of usage of acmeology methodology in the research of psychology of the family is argued for the first time on the base of the systematic, scientific approach. Besides, the attention is concentrated on the possibilities which the usage of general methods, principles and approaches, developed by the mankind at the turn of XXI century, as well as acmeologic methodologic principles. It is found what new things acmeologic approach to psychology is able to give to the cognition of the family. In particular, it is found that the study of the functioning and development of the family in terms of acmeology is based on the identification of the ideal family, according to which the forecasts can be built and the causes of local failure can be explained. It is determined that it will allow family psychologists to diagnose better the interpersonal relationships of family members and to identify family crisis and help to overcome them, that will ensure optimal conditions for the development of the younger generation, optimize the marital relationship and, as a result, will promote the harmonization of personal development. It is shown how the results of researches, conducted in the field of family acmeology, enrich family psychology on practical recommendations of the ways of family improvement as a whole system and improvement of a personality in the family.Keywords: acmeology, family, research methodology, family “acme”, family “cate”.